2018
DOI: 10.4102/sajce.v8i1.522
|View full text |Cite
|
Sign up to set email alerts
|

Absent fathers’ socio-economic status and perceptions of fatherhood as related to developmental challenges faced by children in South Africa

Abstract: How to cite this article: Salami, I.A. & Okeke C.I.O., 2018, 'Absent fathers' socio-economic status and perceptions of fatherhood as related to developmental challenges faced by children in South Africa', South African Journal of Childhood Education 8(1), a522.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
(23 reference statements)
1
8
0
4
Order By: Relevance
“…It provides limited time for the father to seek information about psychosexual development from various sources. Economic improvement is the focus of a father's attention because a father is an economic symbol of the family (Salami & Okeke, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It provides limited time for the father to seek information about psychosexual development from various sources. Economic improvement is the focus of a father's attention because a father is an economic symbol of the family (Salami & Okeke, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study performed in March 2020 in West Surabaya showed that six children aged five years experienced raperape was the form of sexual harassmentby an adult. Father presence has an important role in child's psychosexual development, particularly in building character, identity, sexual orientation, comfort, and confidence (Borisenko & Evseenkova, 2019;Cosson & Graham, 2012;Roskam et al, 2016;Salami & Okeke, 2018). In this paper, father presence defines as direct and indirect existence of father in optimizing psychosexual development of children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, fewer people are getting married (Perelli-Harris & Amos, 2015), many couples cohabit (Perelli-Harris & Styrc, 2018), divorce rates are on the increase (Letamo et al, 2015), and many men and women are choosing to stay single (Lundberg et al, 2016). Yet, it is widely recognised that the involvement of fathers in raising children is beneficial to their well-being and development (Lamb, 2004(Lamb, , 2010Okeke, 2018;Ramotuana & Amone-P'Olak, 2020;Salami & Okeke, 2018). The absence of fathers in the family may influence child outcomes, such as education, social relationships, and behavioural and the emotional well-being of offspring (Mbulayi & Kang'ethe, 2020;Okeke, 2018;Ramotuana & Amone-P'Olak, 2020;Salami & Okeke, 2018;Waldfogel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it is widely recognised that the involvement of fathers in raising children is beneficial to their well-being and development (Lamb, 2004(Lamb, , 2010Okeke, 2018;Ramotuana & Amone-P'Olak, 2020;Salami & Okeke, 2018). The absence of fathers in the family may influence child outcomes, such as education, social relationships, and behavioural and the emotional well-being of offspring (Mbulayi & Kang'ethe, 2020;Okeke, 2018;Ramotuana & Amone-P'Olak, 2020;Salami & Okeke, 2018;Waldfogel et al, 2010). Although the effects of various family types on child outcomes have been studied in Western countries (Hiekel et al, 2014), few such studies have been carried out in African countries, such as Botswana (Dintwat, 2010;Letamo et al, 2015;Maundeni, 2000;Ramotuana & Amone-P'Olak, 2020).…”
Section: Introductionmentioning
confidence: 99%